Challenges and Opportunities in Quality of Indian Higher Education: Examining challenges and opportunities in Indian higher education (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The Indian higher education sector is the third highest in the country, following the United States China. After freedom, India as a developed country has advanced contentiously in the area of education. Higher Education (H.E.) is nowadays one of the foundations of achievement for any sovereign country. Thus it is essential to know the particular challenges and opportunities in the H.E. The goal of this research paper that recognize the particular collection of challenges and opportunities that are evident in the Indian H.E. System. The paper often aims to estimate the level of involvement of the faculty members of H.E. Institutions need to be changed. The survey questionnaire was also structured to include uniform measures of employee engagement, job performance, job engagement, job satisfaction intention to stay. Data has been collected from faculty members of the Banaras Hindu University (BHU) by online survey. This paper is potentially between the very few articles that look into the change required for a faculty member.